Assistive technology using integrated flexible sensor and virtual alarm unit for blood leakage detection during dialysis therapy. Issue 4 (7th October 2016) - Lin, Chia‐Hung; Chen, Wei‐Ling; Li, Chien‐Ming; Wu, Ming‐Jui; Huang, Ping‐Tzan; Chen, Ying‐Shin
Abstract : Blood leakages and blood loss are both serious complications during dialysis therapies. According to dialysis survey reports, these events are life‐threatening issues for nephrology nurses, medical staff, and patients. When venous needle dislodgement occurs, it takes only <2.5 min of reaction time for blood loss in an adult patient, resulting in mortality. As an early‐warning design, a wireless assistive technology using an integrated flexible sensor and virtual alarm unit was developed to detect blood leakage during dialysis therapies. The flexible sensor was designed using a screen print technique with printing electronic circuits on a plastic substrate. A self‐organising algorithm was used to design a virtual alarm unit, consisting of a virtual direct current grid and a virtual alarm driver. In other words, this warning device was employed to identify the blood leakage levels via wireless fidelity wireless network in cloud computing. The feasibility was verified, and commercialisation designs can also be implemented in an embedded system.